2022
DOI: 10.1186/s12888-022-03788-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating family knowledge about sexual health in patients with severe mental illness: a qualitative study in Iran

Abstract: Introduction Although paying more attention to sex education in patients with severe mental illness is recommended in the literature, the role of families has not been specifically clarified.  Aim This study aims to explore family knowledge about sexual health in patients with severe mental illness in Iran. Methods We conducted a total number of 21 interviews with 4 patients, 5 families, 7 psychiatrist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Participants without lived experience of SMI were included in 11 studies [19][105][103][94][82][78][54][50][40][38][33]. These included psychiatric nurses, midwives, administrators of mental health care facilities, caregivers or family members of people with SMI, government decision makers, mental healthcare providers, and people living in communities that include people with SMI.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants without lived experience of SMI were included in 11 studies [19][105][103][94][82][78][54][50][40][38][33]. These included psychiatric nurses, midwives, administrators of mental health care facilities, caregivers or family members of people with SMI, government decision makers, mental healthcare providers, and people living in communities that include people with SMI.…”
Section: Participantsmentioning
confidence: 99%
“…Eight qualitative studies relating to sexuality were identified [40][67][78][90][92][103][105][107]. Stigmatisation was consistently reported by women with SMI and that this was at times perpetuated by healthcare providers.…”
Section: Study Focusmentioning
confidence: 99%